2014
DOI: 10.1245/s10434-013-3441-4
|View full text |Cite
|
Sign up to set email alerts
|

Cosmesis Outcomes for Sector Resection for Ductal Carcinoma In Situ (DCIS)

Abstract: Oncoplastic techniques used for partial mastectomies to provide greater oncological clearance resulted in a high level of patient satisfaction after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
1
6
0
1
Order By: Relevance
“…The majority ( n = 29, 72.5 per cent) did not define ‘delay’, and reported number of days/weeks until radiotherapy, chemotherapy or first adjuvant treatment. A minority of studies ( n = 10, 25.0 per cent) defined delays to adjuvant therapy with varying temporal cut-offs, for example less than or equal to 4 weeks ( n = 2) 15 , 48 , 6 weeks ( n = 4) 8 , 32 , 41 , 67 and 8 weeks ( n = 2) 35 , 68 after operation. Two studies differentiated the cut-off for chemotherapy and radiotherapy as 6 and 8 weeks after surgery, respectively 52 , 69 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority ( n = 29, 72.5 per cent) did not define ‘delay’, and reported number of days/weeks until radiotherapy, chemotherapy or first adjuvant treatment. A minority of studies ( n = 10, 25.0 per cent) defined delays to adjuvant therapy with varying temporal cut-offs, for example less than or equal to 4 weeks ( n = 2) 15 , 48 , 6 weeks ( n = 4) 8 , 32 , 41 , 67 and 8 weeks ( n = 2) 35 , 68 after operation. Two studies differentiated the cut-off for chemotherapy and radiotherapy as 6 and 8 weeks after surgery, respectively 52 , 69 .…”
Section: Resultsmentioning
confidence: 99%
“…Aesthetic outcome was assessed by the patient and clinician ( n = 25, 33.3 per cent) 31 , 36 , 38 , 40 , 42 , 45 , 58 , 65 , 66 , 70 , 76 , 88 , 91–93 , 102 , 103 , 108 , 111 , 112 , 116 , 118–121 , clinician only ( n = 25, 33.3 per cent) 39 , 63 , 68 , 73 , 78 , 79 , 81 , 85 , 96 , 97 , 99–101 , 107 , 113 , 122–126 , patient only ( n = 22, 29.3 per cent) 2 , 47 , 49 , 54 , 64 , 67 , 72 , 74 , 89 , 94 , 109 , 110 , 114 , 117 , 127–135 or was unclear ( n = 2, 2.7 per cent) 95 , 136 . Very few studies ( n = 4) included non-medical staff in aesthetic rating panels …”
Section: Resultsmentioning
confidence: 99%
“…Several authors have noted improved patient satisfaction and outcomes with oncoplastic techniques. 6,25 General satisfaction scores reported by patients reached 87% with immediate flap reconstruction 14,15 Spiegel et al reported that 11 out of 12 (91%) patients graded their result as good to excellent after free flap partial breast reconstruction, with only one grade of "fair" due to dissatisfaction with intra-flap fat necrosis resulting from revision liposuction. 9 With 60 to 70% of early-stage breast cancers treated with BCT and 20 to 30% of them having fair to poor aesthetic outcomes, the number of patients who could benefit from oncoplastic reconstruction is potentially as large as that undergoing mastectomy with reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…It was developed with extensive qualitative input from patients and Rasch psychometric measures [16]. Postoperative modules were later developed to evaluate outcomes after mastectomy without reconstruction [42] and breast-conserving therapy [43][44][45].…”
Section: Breast-qmentioning
confidence: 99%